The defectiveness of the subgroup F adenoviruses in vitro - Tiemessen, Caroline Tanya (My University, 1992)
A distinguishing feature of the human subgroup F adenoviruses, types 40 and,41, is their inability to replicate in cells that permit efficient growth of other adenoviruses, This study was conducted to determine the basis of the viral defect(s) responsible for poor growth in vitro. Cell lines that show different degrees of permissiveness to Ad40 and Ad41 infection were studied for their ability to support a number of key events in the Ad2 life cycle. These events included viral DNA synthesis and packaging, late antigen synthesis, host protein shutoff and viral transcription. The functions were monitored by in vivo labelling of DNA with 32P-orthophosha.te and 3H~thymidine and by dot blot hybridization, ELISA and a fluorescent focus assay, in vivo labelling of proteins with 35S-methionine, and RNA:DNA dot hybridizations and RT-PCR, respectively. Complementation of Ad41 by Ad2 was monitored using a fluorescent focus assay. Transfection assays performed with plasmids containing defined Ad2 early region DNA were monitored for their ability to complement Ad40 and Ad41 in the same way. The complexity of the growth patterns seen by the subgroup F adenoviruses suggests that defectiveness is a multi-factorial phenomenon, and not easily explained by a single aberrant function. Interferon induction in response to subgroup F adenovirus infection was excluded as a possible factor in limited virus growth in culture. In contrast to Ad2, Ad40 and Ad41 were sensitive to interferon in Chang cells. Both the sensitivity to interferon in Chang cells as well as the growth defect in HEF cells could be overcome in mixed infection with Ad2. Differences observed in the ability of Ad40 and Ad41 to synthesize DNA in non-permissive cells, and to produce free hexon antigen in epithelial cell lines suggests that there may be replicative defects in subgroup F adenoviruses which are not shared by both serotypes, The block in replication of Ad41 and Ad40 in HEF cells appeared to occur during the early and late phases of the infectious cycle, respectively.
Keywords: Adenoviridae.; Adenovirus Infections, Human.